Supplementing a typology of curation: Learning from George Harrison and Indian music - Jones, Michael Lewis (Popular Music History, 2021)
The article explores the creation of a concert that explored George Harrison’s relationship with Indian classical music. It was a scripted concert that featured two surviving musicians from the ‘Within You Without You’ recording sessions along with material artefacts. The experience is used to consider supplements to the Baker, Istvandity and Nowak identification of structuring concepts of curation.